Qualitative Student Mobility Research in Canada: Existing Contributions and Scholarly Recommendations - Aurini, Janice; LaCroix, Emerson; Iafolla, Vanessa; Brisbane, Maria; Dreesha, Mrittika (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2025)
This article presents the qualitative complement to Pizarro Milian and Zarifa’s (2021) analysis of Canadian quantitative research on student transfer and mobility. Drawing on 75 qualitative peer-reviewed articles and institutional reports published between 1991 and 2022, we summarize the main findings and outline the data and methodological gaps in the literature. To strengthen the rigour and broaden the applicability of Canadian qualitative research on student mobility, we emphasize the need to employ a variety of methodological strategies, including multi-site, comparative, and longitudinal qualitative research.